2014
DOI: 10.1007/s11033-014-3613-8
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism of CYP3A5*3 contributes to clopidogrel resistance in coronary artery disease patients among Tamilian population

Abstract: Clopidogrel is an antiplatelet drug. It is used for the treatment as well as for the prophylaxis of coronary artery disease. Clopidogrel resistance is an emerging problem in clinical settings. The aim of the present study was to evaluate the effect of CYP3A5*3 genetic polymorphism on clopidogrel resistance. One hundred and forty-seven patients from outpatient Department of Cardiology on 75 mg/day of clopidogrel as maintenance dose were recruited from April 2010 to July 2011. All subjects gave written informed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…SNPs may affect clopidogrel activation, which could also contribute to the adverse events of this prodrug. Variant alleles and genotypes of CYP3A5*3 polymorphism contributed significantly to clopidogrel resistance with a higher OR 32) . Suh et al 33) also revealed an increased frequency of atherothrombotic events within six months after coronary angioplasty in patients with the CYP3A5 nonexpression genotype ( CYP3A5*3 ).…”
Section: Discussionmentioning
confidence: 99%
“…SNPs may affect clopidogrel activation, which could also contribute to the adverse events of this prodrug. Variant alleles and genotypes of CYP3A5*3 polymorphism contributed significantly to clopidogrel resistance with a higher OR 32) . Suh et al 33) also revealed an increased frequency of atherothrombotic events within six months after coronary angioplasty in patients with the CYP3A5 nonexpression genotype ( CYP3A5*3 ).…”
Section: Discussionmentioning
confidence: 99%
“…43) Evidence also revealed that CYP3A5*3 was associated with clopidogrel response and clinical outcomes. [44][45][46] Currently, few studies investigated the association of genetic polymorphisms with ticagrelor response. The polymorphisms in P2Y12, P2Y1, and ITGB3 have no effect on platelet aggregation in ticagrelor-treated patients with atherosclerotic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al, for example, concluded that CYP3A5 genetic status plays an important role in the clinical efficacy of clopidogrel in a prospective cohort study involved 1258 Caucasian patients; out of which the wild type number was 509 and the variant CYP3A5*3 was 749 [35]. Among the Tamil population, it was found that a single nucleotide polymorphism (SNP) of the cytochrome CYP3A5*3 contributes to clopidogrel resistance [36].…”
Section: Allelic Distribution and Clopidogrel Responsiveness On Clinimentioning
confidence: 99%